Who Is Doing the Housework in Multicultural Britain? - Kan, Man-Yee and Laurie, Heather (Sociology, 2018)
There is an extensive literature on the domestic division of labour within married and cohabiting couples and its relationship to gender equality within the household and the labour market. Most UK research focuses on the white majority population or is ethnicity ‘blind’, effectively ignoring potentially significant intersections between gender, ethnicity, socio-economic position and domestic labour. Quantitative empirical research on the domestic division of labour across ethnic groups has not been possible due to a lack of data that enables disaggregation by ethnic group. We address this gap using data from a nationally representative panel survey, Understanding Society, the UK Household Longitudinal Study containing sufficient sample sizes of ethnic minority groups for meaningful comparisons. We find significant variations in patterns of domestic labour by ethnic group, gender, education and employment status after controlling for individual and household characteristics.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDM4MDM4NTE2Njc0Njc0